Gerakan Penguatan Literasi dan Numerasi melalui Kegiatan Ekstrakurikuler di SD 040536 Partibi Lama - Agusmanto Hutauruk; Henny I. Sitanggang; Santa Miralda Lumbantobing; Magdalena Siahaan; Mika Oktavia Purba; Sarah Yulita; Enda Ristauli Tumanggor (Universitas 17 Agustus 1945 Semarang, 2023)
This Community Service Program aims to strengthen literacy and numeracy in elementary school (SD) students where the focus is to provide assistance to students about the importance of strengthening literacy and numeracy in students. This activity was carried out by lecturers and students from the Mathematics Education Study Program and the Economics Education Study Program, the Teaching and Education Faculty, HKBP Nommensen University Medan. The implementation of Community Service activities in strengthening literacy and numeracy in students began on 06 February 2023 and ended on 25 February 2023. Previously, this Community Service activity had been socialized to students of SD Negeri 040536, in every classroom and it was seen that the cause of the lack of literacy and numeracy in students is still low due to lack of learning and arithmetic exercises. This problem was then minimized by carrying out related Community Service Program activities to strengthen literacy and numeracy for elementary school students. This program is an important matter in efforts to improve the concept of numeracy in schools.